AKIBAT HUKUM TERHADAP WANPRESTASI DALAM PERJANJIAN DIBAWAH TANGAN ATAS JUAL BELI TANAH DAN BANGUNAN BERDASARKAN PASAL 1320 KUHPERDATA - Ummam, Khoirul; Deny Guntara; Muhamad Abas (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
An agreement is an event that is carried out by a person to another person, either one party or several parties, the agreement then becomes a law for the parties who have made it. The transfer of land rights can be transferred and the transfer of land rights due to inheritance, buying and selling, exchange, grants, and wills. Research conducted by the author on this issue is related to Default in the transfer of rights to land and building houses. The purpose of this study is to determine legal protection and certainty in the transfer of land and building rights in private agreements based on Article 1320 of the Civil Code and related to Law Number 5 of 1960 concerning Agrarian Principles. And to find out the considerations of the Panel of Judges in Decision Number 60/Pdt.G/2022/PN Kwg. With qualitative research methods, normative juridical approach methods using secondary data as primary data, and primary data as supporting data, and analysis techniques using legal reasoning, as well as the results of research conducted that the transfer of rights to land and buildings has a process that needs to be carried out, if If the transfer of rights is through a sale and purchase, then the sale and purchase agreement must be before the Land Deed Making Officer, who then makes a sale and purchase deed, and the transfer of rights is registered at the land office for the transfer of new rights.